CHOOSING EQUITY AS A SOURCE OF FINANCE: PERCEPTION OF SME PROMOTERS - Ansita Aggarwal; Satya Ranjan Acharya (Copernican Journal of Finance & Accounting, 2020)
This paper tries to understand the perception of SMEs’ promoters in choosing equity as one of their sources of finance. To explore reasons the research has been done in five phases which included: a literature review, offer document objectives, ratio analysis, and in-depth interviews of five SME owners of Gujarat. In the last phase, all the reasons have been simplified by including them in five broad themes. The study analyzed the five broad themes as bank loan barriers, financial factors, growth factors, economic factors, and other barriers. The research has been carried in Gujarat so there is a need for further research all over India. This is going to help SMEs in understanding the pros and cons of selecting a particular avenue as a source of finance. SMEs are the engine of most of the developing nations. This makes it necessary to study them in detail so that the environment can be made friendly for them.